Penentuan Kadar Amonia (NH3) pada Limbah Cair K-34 dalam Rangka Pengendalian Pencemaran Lingkungan - Gova, Muhammad Agil (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2018)
Free Ammonia is an ammonia did not react perfectly with Carbon Dioxide in the process when producing urea. Free ammonia did not bond with urea directly but it bonded in grain. This reaserch purposed to know how to determine Ammonia’s degree, to know how to use Spektrofotometer to look for the value of Ammonia absorbance, and to know how to make Reagent Nessler A. The method for this research is method which combine qualitative and quantitative by checked the change color of the sample, which is the sample has been reacting with Reagent Nessler A. This reaserch used Spektrofotometer Uv-Vis as an instrument to detemine Ammonia absorbance. The average result of Ammonia (NH3) degree in canal 34 it was site the third Pusri it was gotten 186 ppm, and the average of pH Ammonia (NH3) for canal 34 was 8,34, and the highest average of Ammonia (NH3) degree was 280 ppm and the highest pH Ammonia (NH3) is 9,2. All of the result were in quality standard based on Ministry regulation no. 5 which issued in 2014.